Kajian sistem pengelolaan lingkungan stasiun pengisian bahan bakar umum di Manokwari - Christmas Yulian Sonya Marola; Nurhaidah I. Sinaga; B.M.G. Sadsoetoeboen (Program Pascasarjana Universitas Papua, 2018)
This research was designed to describe the environmental management system employed by public station petroleum at Manokwari, using variables of their implementation to public petroleum station regulations, environmental policies, structural and official/personal organization, environmental protection facilities, procedures, and water waste management. The results show that implementations for public petroleum station regulation, SPBU 84.983.01 and 84.983.02 are relatively good, or good management, but SPBU 81.983.05 is fairly good or environmental management is good enough. SPBU 84.983.01 and SPBU 81.983.05 have good enough for structural or personal organization, and SPBU 84.983.02 is good for its structural and personal organization. Others aspects of physical and environmental protection facilities SPBU 84.983.02 is good, while SPBU 84.983.01 is fairly good. Another public station petroleum of SPBU 81.983.05 is not fulfillment the physical and environmental protection facilities or under good criteria. Water quality usages for monitoring tanks of all public stations petroleum are fulfilled the standard. However, the water quality released from the public station petroleum to drainages, rivers, or sea are not fulfilled the water and sanitation standards.